Refleksi Hari Pendidikan Nasional 2025 : Sekolah Rakyat dan Kurikulum Deep Learning - Maryono Maryono; Robingun Suyud El Syam; Salis Irvan Fuadi (Jurnal Pendidikan dan Sastra Inggris, 2025)
The article aims to describe the reflection of National Education Day 2025 regarding the People's School and the Deep Learning Curriculum, where previous researchers have not been specific to this aspect. This research is a qualitative setting with descriptive analysis and relates it to theory. The findings show that National Education Day 2025 is a moment of deep reflection on the nature of education as a process of humanization of humans. Education is not just academic, but is a cultural means to educate the life of the nation and form an enlightened civilization. The "People's School" policy needs to be reviewed. Although the goal is noble, namely to provide access to education for children from poor families, in practice it opens up the potential to perpetuate dualism and discrimination in education. The Deep Learning curriculum is claimed to be able to answer the challenges of the 21st century through three approaches: deep understanding, mindful learning and joyful learning. The urgency of rote learning as the basis for long-term memory needs to be considered to complement the three approaches. We offer authentic assessment using various relevant methods and instruments, considering the elimination of the Minimum Completion Criteria (KKM) which is considered not an authentic value (pulley). The value pulley gives an inaccurate picture of student abilities, also reduces student learning motivation and triggers dishonesty.